2023
DOI: 10.1111/pcn.13523
|View full text |Cite
|
Sign up to set email alerts
|

A circuit‐based approach to modulate hypersexuality in Parkinson's disease

Abstract: Aim: Impulse-control disorder is a common neuropsychiatric complication in Parkinson's disease (PD) under dopamine replacement therapy. Prior studies tested the balance between enhanced desire towards reward and cognitive control deficits, hypothesized to be biased towards the former in impulse control disorders. We provide evidence for this hypothesis by measuring behavioral and neural patterns behind the influence of sexual desire over response inhibition and tools towards functional restoration using repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In contrast, the underlying changes mediating impulsive-like behavior can be attributed to anatomical reductions in cognitive control areas found in the current study, including the medial prefrontal cortex and pre-SMA. Indeed, abnormal activity of the dorsal medial PFC and pre-SMA areas has been reported in PD + ICD [ 29 ], associated with abnormal control in PD + ICD due to its role in executive control and response inhibition [ 30 ]. An alternative non-exclusive view would entail that the reduced GM density in the pre-SMA participate in the co-occurrence of dysfunctional changes in various behavioral roles mediated via limbic structures [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the underlying changes mediating impulsive-like behavior can be attributed to anatomical reductions in cognitive control areas found in the current study, including the medial prefrontal cortex and pre-SMA. Indeed, abnormal activity of the dorsal medial PFC and pre-SMA areas has been reported in PD + ICD [ 29 ], associated with abnormal control in PD + ICD due to its role in executive control and response inhibition [ 30 ]. An alternative non-exclusive view would entail that the reduced GM density in the pre-SMA participate in the co-occurrence of dysfunctional changes in various behavioral roles mediated via limbic structures [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings could provide compelling evidence for further comprehending the neurophysiological mechanism of ICD and might provide candidate brain targets for non-invasive neuromodulation. As the recent clinical trial reported, excitatory neuromodulation over the pre-supplementary motor area was successfully applied to improve response inhibition in PD-ICD patients (Mata-Marin et al, 2022). Some limitations must be mentioned.…”
Section: Discussionmentioning
confidence: 99%